Pengembangan Instrumen Penilaian Kinerja (Performance Assessment) Praktikum Konsep Dasar IPA Berbasis Karakter Untuk Mengukur Kemampuan Proses Sains Mahasiswa PGSD Fakultas Ilmu Pendidikan Universitas Negeri Makassar - muhammad irfan; muslimin muslimin (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This research is a research development that aims to produce a practical performance assessment instrument of Character-based Basic Concept of Science to measure the ability of the science process of PGSD FIP UNM Students. Specifically, the performance appraisal instruments produced were the performance instruments of the science practicum to assess the ability of the Science Process Science of PGSD FIP UNM Students. The results of the assessment of experts/experts and practitioners to assess the suitability between material, construction, and language on each item of the assessment instrument indicate that the device that has been developed has fulfilled valid and reliable criteria. The results of the simulation and the readability test show that the instrument can be read and understood clearly by the user so that it can be used to assess the performance of the Student practicum. The effectiveness test results show that; (1) data about the lecturers '(colleagues') responses to the practicum performance appraisal (readability test) is in the very good category; (2) the results of the observation sheet using practicum performance appraisal tools filled in by observers minimally carried out all, (3) practicum performance value data can be described in accordance with the assessed criteria and, (4) student responses to positive learning tools (practical guides). Thus, the Physics Practicum performance appraisal instrument has fulfilled valid and reliable criteria and can be used efficiently and efficiently by Lecturers and Students of PGSD UNM Study Program.